2008
DOI: 10.1016/j.cmet.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The Acyclic CB1R Inverse Agonist Taranabant Mediates Weight Loss by Increasing Energy Expenditure and Decreasing Caloric Intake

Abstract: Cannabinoid 1 receptor (CB1R) inverse agonists are emerging as a potential obesity therapy. However, the physiological mechanisms by which these agents modulate human energy balance are incompletely elucidated. Here, we describe a comprehensive clinical research study of taranabant, a structurally novel acyclic CB1R inverse agonist. Positron emission tomography imaging using the selective CB1R tracer [(18)F]MK-9470 confirmed central nervous system receptor occupancy levels ( approximately 10%-40%) associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(191 citation statements)
references
References 59 publications
14
176
0
1
Order By: Relevance
“…These trials consistently found that 1 year of treatment with rimonabant 20 mg significantly increased weight loss and reduced waist circumference compared with diet or lifestyle therapy alone (Table 1). A double-blind, placebo-controlled, 12-week study of another CB 1 receptor inverse agonist, taranabant, in 358 obese/overweight adult completers, reported that weight loss was increased and waist circumference reduced at all evaluated doses (0.5, 2, 4 and 6 mg/day) compared with placebo [75]. Very importantly, in a subgroup of patients who received only a single dose (12 mg) of taranabant, there was a significant reduction (27%) in energy intake over 24 h, and an increase of energy expenditure (measured as a decrease in mean respiratory quotient, and suggestive of lipid metabolism) over 5 h post-dosing [75].…”
Section: Studies In Obese Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These trials consistently found that 1 year of treatment with rimonabant 20 mg significantly increased weight loss and reduced waist circumference compared with diet or lifestyle therapy alone (Table 1). A double-blind, placebo-controlled, 12-week study of another CB 1 receptor inverse agonist, taranabant, in 358 obese/overweight adult completers, reported that weight loss was increased and waist circumference reduced at all evaluated doses (0.5, 2, 4 and 6 mg/day) compared with placebo [75]. Very importantly, in a subgroup of patients who received only a single dose (12 mg) of taranabant, there was a significant reduction (27%) in energy intake over 24 h, and an increase of energy expenditure (measured as a decrease in mean respiratory quotient, and suggestive of lipid metabolism) over 5 h post-dosing [75].…”
Section: Studies In Obese Animalsmentioning
confidence: 99%
“…This needs to be taken into account when prescribing CB 1 The treatment group received an oral dosage of 20 mg/day for 1 year a Occurring in ≥2% of the rimonabant (20 mg) group and in ≥1% of the placebo group b Incidence increased by >0.5% between placebo group and rimonabant (20 mg/day) group Based on data from [78] antagonists to patients with obesity and type 2 diabetes, particularly since depression and anxiety are often described as accompanying these disorders, and weight loss per se can induce mood disturbances [65]. A similar, albeit not completely overlapping, safety profile emerges from the Phase II trial on taranabant [75], although in this case the smaller number of patients participating in the study did not allow any definitive conclusion to be drawn. In summary, CB 1 receptor antagonists/inverse agonists are emerging as efficacious and relatively safe therapeutic drugs against not only obesity, but also type 2 diabetes and associated cardiometabolic risk factors.…”
Section: Studies In Obese Animalsmentioning
confidence: 99%
“…11,[23][24][25] Although the molecular basis and cellular basis for the action of inverse agonists have been well documented and the physiological endpoints are well defined, the detailed physiological mechanisms through which modulation of CB1R translate to changes in peripheral tissue metabolism can be difficult to dissect. The following sections will address the physiological MOA related to the site of action for inverse agonists and the physiological pathways involved.…”
Section: Molecular and Cellular Moamentioning
confidence: 99%
“…Food intake reduction and energy expenditure increase are two important components of the MOA of taranabant, 11,25 and both of these pharmacodynamic effects can lead to reduction of fat mass and liver lipid content. Food intake reduction and energy expenditure increase have also been shown in rodents for rimonabant or AVE1625.…”
Section: Peripheral Physiological Effects Vs Peripheral Site Of Actiomentioning
confidence: 99%
See 1 more Smart Citation